PENGARUH PELATIHAN DAN KREATIVITAS TERHADAP PENGEMBANGAN USAHA CV SITA KONVEKSI SABLON DAN BORDIR JELUTUNG KOTA JAMBI - fadila; Sucipto; Khairiyani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This study aims to determine and analyze the influence of training and creativity on the business development of CV Sita Convection Screen Printing and Embroidery in Jelutung, Jambi City. The research employs a quantitative approach. The number of samples in this study consists of 31 workers from CV Sita Convection, and the technique used is nonprobability sampling, specifically saturated sampling. Data collection methods include observation, interviews, documentation, and questionnaires. The data analysis technique used is multiple linear regression analysis. The results of the study indicate that training has a positive and significant impact on business development, while creativity does not have a significant effect on business development. Based on the data analysis in this study, the regression value for the training variable is 0,823, while the regression value for the creativity variable is 0,092. The analysis shows that both variables significantly contribute to business development, with the total contribution of the training and creativity variables amounting to 30% of the observed variability in this study.